Addressing The Shortage Of Nurses In Malaysia - Harjit Kaur, Ujagar Singh * (CodeBlue, 2023)
MOH’s decision to allow private hospitals to hire foreign nurses will provide some relief to our health care system, but it could raise health care costs. Offering foreign nurses competitive packages may also lead to pay disparities with local nurses.